Application Research of Project-based Teaching Based on Working Process in Oracle Database Teaching. Issue 1 (February 2020) - Cai, Xiaoyan; Shen, Wei; Cui, Yanping; Meng, Xianyu; Zhang, Weiqing; Yan, Zhizhi
Abstract: This paper combines the design and development of student management system and integrates project-based teaching based on working process into the course of Oracle database technology. It guided by the working process and regarding the project as the carrier, and in accordance with the principle of "task-driven, practice-connected, work-integrated and strengthening ability", combing the online and offline teaching integrates with "teaching, learning and doing", fully arouses students' learning enthusiasm and initiative, and enhances their comprehensive ability and sustainable development ability.